Synthesis of Sulochrin-125I and Its Binding Affinity as α-Glucosidase Inhibitor using Radioligand Binding Assay (RBA) Method - W. Lestari; V.Y. Susilo; S. Setiyowati; Triningsih Triningsih; A. Ariyanto; P. Widayati; L.B.S. Kardono; A. Yanuar (PPIKSN-BATAN, 2014)
Most of diabetes patients have type 2 diabetes mellitus or non insulin dependent diabetes mellitus. Treatment of type 2 diabetes mellitus can be conducted by inhibiting the α-glucosidase enzyme which converts carbohydrates into glucose. Sulochrin is one of the potential compounds which can inhibit the function of α-glucosidase enzyme. This study was carried out to obtain data of sulochrin binding with α-glucosidase enzyme as α-glucosidase inhibitor using Radioligand Binding Assay (RBA) method. The primary reagent required in RBA is the labeled radioactive ligand (radioligand). In this study, the radioligand was sulochrin-125I. Prior to the sulochrin-125I synthesis, sulochrin-I was synthesized. Sulochrin-I and sulochrin-125I were synthesized and their bindings were studied using RBA. The molecular formula of the synthesized Sulochrin-I is C17H15O7I and its molecular weight is 457.9940. The sulochrin-125I was synthesized from sulochrin-I by isotope exchange method. From RBA, the dissociation constant (Kd) and the maximum binding (Bmax) were found as 26.316 nM and 9.302 nM, respectively. The low Kd indicates that sulochrin is capable of binding to α-glucosidase.Received: 08 November 2013; Revised: 28 February 2014; Accepted: 28 March 2014